Comparison of the accuracy of intraoral scanning systems with conventional impression in dentate patient - İmadettin Alsayed; Yılmaz Umut Aslan (Selcuk Dental Journal)
Background: Over the last years, different intraoral scanning systems for direct digitalization have been introduced to the dental market. However, the accuracy of these scanners is variable, and little information is available. The aim of this in vivo study was to compare the accuracy of two intraoral scanning systems and the difference between upper and lower jaw on the accuracy.Methods:10 patients with full dentition received one conventional impression with polyvinyl siloxane(Elite HD+, Zhermack SpA, Italy)and three scans with CEREC OC (Sirona Dental Systems, Sirona, Bensheim, Germany) and Straumann CARES IOS (Intra oral Scanner, Basel, Switzerland)for upper and lower jaw. The conventional impresions were poured and the casts made from it were scanned and used as the reference model  to evaluate precision and trueness of intraoral scanning virtual models provided by each system. Digital models were analyzed with a software (Geomagic Control;Geomagic, Morrisville,USA).Results:The trueness value was 99.88±42.56μmin upper jaw and 82.6±26.81 μmin lower jaw for CEREC OC, and 105.53±25.49 μmin upper jaw,and 109.56±36.84 μmin lower jaw for CARES IOS. The differences between two systems were not statistically significant (P>0.05), but statistically significant difference was found in the precision (P<0.05). CEREC OC showed higher value in both upper and lowerjaws.Conclusion:CEREC OC was more precise than CARES IOS and at the similar level of trueness. No statistically significant difference was found between upper and lower jaws in both systems.Key Words: Intraoral scanning, STL, Accuracy, CAD/CAM